Gut-Lung Axis - Anggie Indari; Menaldi Rasmin; Ari Fahrial Syam (Indonesian Society of Respirology (ISR), 2023)
Microbiota and the body's immune system have a two-way interaction that is interconnected. The microbiota plays a role in the formation and maturation of the immune system, on the other hand, the immune system shapes the composition and function of the microbiota. This interaction is important in maintaining the body’s immune system’s homeostasis. The human intestine contains various types of microbes that form the gut microbiota. Various studies have found that changes in the gut microbiota are associated with immunity in distal tissues such as the lung. This gives rise to the concept of a feedback relationship between the gut and lung organs called the gut-lung axis. Through this axis, changes in the composition of the gut microbiota not only cause abnormalities in the gut but also affect microbiota in the lungs and can cause disease. One of the important routes in the transmission of substances from the intestine is through the mesenteric lymphatics. Probiotics can help improve the gut’s defense mechanism. A high-fiber diet can also reduce pathogenic bacteria by increasing levels of short-chain fatty acids. Therefore, a healthy lifestyle is needed to maintain the balance of the microbiota.